Microclimate of coconut varieties and cacao and cinnamon grown as mixed crops with coconut - BALAKRISHNAN, T. K.; NAIR , P. K. R.; NELLIAT, E. V. (MAUSAM, 1976)
During the peak period of evaporation (December-May) when evaporation from the open surface (observatory) exceeded 5 mm/day, the corresponding values for the microclimate of cacao and cinnamon, during the early stages of their growth as mixed crops with coconut palms, were 2-4 mm. The diurnal variations in relative humidity and vapour pressure in the microclimate of cacao and cinnamon were relatively much less compared to those of observatory and microclimate of coconut. There were no differences in the microclimate of tall and dwarf varieties of coconut at their full bearing stage.